Western Cultural Identification Explains Variations in the Objectification Model for Eating Pathology Across Australian Caucasians and Asian Women - Tan, Charmain S.; Fuller-Tyszkiewicz, Matthew; Utpala, Ranjani; Yeung, Victoria Wai Lan; De Paoli, Tara; Loughan, Stephen; Krug, Isabel (Frontiers in Psychology, 2016)
Objective: To assess differences in trait objectifying measures and eating pathology between Australian Caucasians and Asian women living in Australia and in Hong Kong with high and low levels of western cultural identification (WCI) and to see if exposure to objectifying images had an effect on state-objectification. A further aim was to assess using path analyses whether an extended version of the objectification model, including thin-ideal internalisation, differed depending on the level of WCI. Method: A total of 424 participants comprising 162 Australian Caucasians and 262 Asians (n=183 currently residing in Australia and n = 79 living in Hong Kong) took part in the study. Of the overall Asian sample, 133 individuals were classified as high-WCI and 129 participants as low-WCI. Participants were randomly allocated into one of two conditions, presenting either objectifying images of attractive and thin Asian and Caucasian female models (objectification group, n=204), or showing neutral images of objects (e.g. chairs, tables; control group, n=220). Subsequently, participants were asked to complete a series of questionnaires assessing objectification processes and eating pathology. Results: Findings revealed that the Caucasian group presented with significantly higher internalisation and body surveillance scores than either of the two Asian groups and also revealed higher scores on trait-self-objectification than the low-WCI Asian sample. As regards to the effects of objectifying images on state self-objectification, we found that ratings were higher after exposure to women than to control objects for all groups. Finally, multi-group analyses revealed that our revised objectification model functioned equally across the Caucasian and the high-WCI Asian group, but differed between the Caucasian and the low-WCI Asian group. Conclusions: Our findings outline that individuals with varying levels of WCI might respond differently to self-objectification processes. Levels of WCI should therefore be taken into consideration when working with women from different cultural backgrounds.